1111 Type I interferon and neutrophil transcripts in lupus nephritis renal biopsies: Clinical and histopathological associations. (14th December 2022) - Mavragani, Clio P; Kirou, Kyriakos A; Seshan, Surya V; Crow, Mary K
Abstract : Objectives: To investigate the expression of type I interferon (IFN-I) and neutrophil transcripts in kidney tissue from patients with distinct classes of lupus nephritis and their association with clinical and histopathological features. Patients and Methods: Quantitation of IFN-I and defensin-α3 transcripts was performed in kidney biopsies from 24 patients with various classes of lupus nephritis (6 class III, 14 class IV, 4 class V) and 3 control samples by real-time PCR. Demographic characteristics, creatinine levels, and histopathological characteristics, including activity and chronicity indices, presence of active glomerular lesions, and tubulointerstitial or vascular involvement were analyzed. Results: IFNα2 and β transcripts were overexpressed in renal tissues from patients with proliferative forms of lupus nephritis (III/IV) compared to patients with membranous nephritis and control kidneys. Such difference was not detected between membranous nephritis and control biopsies. Defensin-α3 transcripts, overexpressed in lupus nephritis biopsies – particularly those with segmental necrotizing lesions - were correlated with higher activity index (r=0.61, p=0.02). Patients with proliferative lupus nephritis with impaired renal function, as attested by elevated creatinine levels, displayed higher relative expression of IFNα2 transcripts in renal tissues compared to those with normal renal function (26.6 ±18.0 vs. 7.1 ±6.2, p=0.013). Conclusion: IFN-I transcripts are produced locally in kidneys from patients with the proliferative, but not membranous, forms of lupus nephritis in association with impaired renal function. Neutrophil transcript defensin-α3 is a potential biomarker for increased renal pathologic activity. These findings provide insight into mechanisms of proliferative lupus nephritis and could impact therapeutic decisions in clinical practice.